Understanding Social Factors in the Context of Trauma: Implications for Measurement and Intervention. Issue 8 (13th September 2016) - Wagner, Anne C.; Monson, Candice M.; Hart, Tae L.
ABSTRACT: One of the most important factors predicting the presence of posttraumatic stress disorder (PTSD) after trauma exposure is social support, yet the construct is theoretically complex and remains variably defined. To better inform the trauma literature on the impact of social factors, a theoretical review of social support and PTSD was conducted, and implications for measurement and intervention are outlined. Type of trauma, sex of participant, timing of social support, and support providers are described as significant moderators of the association between social factors and PTSD. The developmental trajectory of the association between social factors and PTSD occurrence is outlined, emphasizing the positive influence of social support initially following trauma, and the deterioration effect of PTSD symptoms on social support over the longer term. Possibilities for future research and intervention at multiple levels and at different time points are described.